Metabolic Stress and Compromised Identity of Pancreatic Beta Cells - Swisa, Avital; Glaser, Benjamin; Dor, Yuval (Frontiers in Genetics, 2017)
Beta cell failure is a central feature of type 2 diabetes (T2D), but the molecular underpinning of the process remains only partly understood. It has been suggested that beta cell failure in T2D involves massive cell death. Other studies ascribe beta cell failure to cell exhaustion, due to chronic oxidative or endoplasmic reticulum stress leading to cellular dysfunction. More recently it was proposed that beta cells in T2D may lose their differentiated identity, possibly even gaining features of other islet cell types. The loss of beta cell identity appears to be driven by glucotoxicity inhibiting the activity of key beta cell transcription factors including Pdx1, Nkx6.1, MafA and Pax6, thereby silencing beta cell genes and derepressing alternative islet cell genes. The loss of beta cell identity is at least partly reversible upon normalization of glycemia, with implications for the reversibility of T2D, although it is not known if beta cell failure reaches eventually a point of no return. In this review we discuss current evidence for metabolism-driven compromised beta cell identity, key knowledge gaps and opportunities for utility in the treatment of T2D.